Comparative Study on Mechanical Properties of Waste Composite Materials for Bricks Application - Siswanti Zuraida; Andrie Harmaji; Sastita Pratiwi; Xevna De Elshinta Arellsya Ruitan; Astrid Nadya Anggraini; Yudea Sisti Kurniadevi; Bart Julien Dewancker (Universitas Negeri Malang, 2022)
This study discusses mechanical properties and analysis of composite materials to develop building bricks for structural lightweight concrete replacement applications made from three different waste materials, i.e. sawdust, polyethylene terephthalate (PET) plastic bottle, and used diaper. All waste materials are used to mixture composite, as cement replacement, with a mixture of 0, 5, 10, 15, and 20 percent of the total weight. This study uses a quantitative method with the sample used as cylindrical tube with 20 mm of diameter and 40 mm of height. Tests were carried out in the form of compressive and specific gravity tests to determine the mechanical and physical properties of the composite material. The use of waste materials as mixtures for composite manufacture with a water per cement ratio of 0.4 at the age of 28 days results in the best compressive strength of 20.70 MPa (5 percent of sawdust), 33.04 MPa (5 percent of PET), and 18.05 MPa (5 percent of used diaper). The density value shows that the addition of waste materials tends to decrease the weight of the composite result. Based on these results, it can be concluded that the use of waste composite materials is a potential replacement for lightweight structural concrete as an effort to reduce the cement requirement for building material applications.DOI: 10.17977/um024v7i22022p092